2016
DOI: 10.1161/jaha.115.002706
|View full text |Cite
|
Sign up to set email alerts
|

Galectin‐3 Is Elevated and Associated With Adverse Outcomes in Patients With Single‐Ventricle Fontan Circulation

Abstract: BackgroundGalectin‐3 may play a role in cardiac and noncardiac fibrosis, and elevated circulating levels of this protein predict adverse outcomes in patients with heart failure who do not have congenital heart disease. We investigated galectin‐3 in adults with single‐ventricle Fontan circulation, patients who are prone to premature clinical deterioration in the context of extensive multiorgan fibrosis.Methods and ResultsWe measured plasma galectin‐3 concentrations in 70 ambulatory adult Fontan patients and 21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…In 70 ambulatory adult Fontan patients, Opotowsky et al 20 showed that galectin-3 levels were associated with adverse outcomes. In this study, NT-proBNP was not measured, and the association of galectin-3 with adverse outcomes was adjusted one by one for age, NYHA functional class, estimated glomerular filtration rate, C reactive protein and the presence of chronic comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…In 70 ambulatory adult Fontan patients, Opotowsky et al 20 showed that galectin-3 levels were associated with adverse outcomes. In this study, NT-proBNP was not measured, and the association of galectin-3 with adverse outcomes was adjusted one by one for age, NYHA functional class, estimated glomerular filtration rate, C reactive protein and the presence of chronic comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…15 None of the patients enrolled had been hospitalised in the prior 30 days. Exclusion criteria included two-ventricle repair or cardiac transplantation subsequent to Fontan procedure, known kidney disease or recent creatinine >2 mg/dL.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have identified GFAP as an early marker of brain injury among children undergoing surgery for congenital heart defects. Although related to many important poor outcomes, 15,24 it might not be associated with pediatric unplanned readmission or mortality. There is an increasing focus to identify children at greater risk of readmission after congenital heart surgery.…”
Section: Commentmentioning
confidence: 99%